Determination of the 137Cs and 90Sr radioisotope activity concentrations found in digestive organs of sheep fed with different feeds - Baskaya, Halime; Dogru, Mahmut; Kucukonder, Adnan (Elsevier Sci Ltd, 2014)
In this study, 12 weanling lambs were fed for 6 months at the Vetenary Control and Research Institute of Elazig in Turkey. Sheep were divided into two groups according to feeding type. Each group of sheep was fed a different amount of feed. The activity concentrations of Cs-137 and Sr-90 were determined in rumen, small intestine and large intestine tissue samples of sheep fed various feeds and quantities. Transfer coefficients and concentration ratios were estimated. The highest average Cs-137 and Sr-90 activity concentrations were 82 +/- 22 Bq kg(-1) fw in the straw group small intestine sample and 74 +/- 9.0 Bq kg(-1) fw in the fresh lucerne group rumen sample, respectively. Radioactivity levels for Cs-137 and Sr-90 are under the maximum permitted radioactive pollution level for all the samples. The transfer coefficient of 137Cs and 90Sr in the samples of sheep ranged from 1.0 x 10(-1) to 2.1 x 100 d kg-1 and 1.7 x 10(-1) to 2.3 x 10(0) d kg(-1), respectively. Calculated transfer coefficients of Sr and 137Cs in the samples of sheep were higher than the expected values. Geometric means of Ff and CR for Cs-137 were maximum in the fresh lucerne group large intestine sample. Geometric means of F-f and CR for Sr-90 were maximum in the fresh lucerne group small intestine sample. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Radioactivity; Cs-137; (90) Sr; Sheep; Transfer coefficient; Concentration ratio